Low line density blazed gratings with low blaze angles. Issue 1 (1st December 2022) - Lemke, S; Alimov, S; Knedel, J; Kutz, O; Rudolph, I; Seliger, T; Sokolov, A
Abstract: Gratings installed in synchrotron beamlines and instruments have standard line densities ranging from 300 L/mm up to 2400 L/mm with blaze angles from 0.3° to 2°. For FEL beamlines lower line densities and lower angles are required. To manufacture these in the required high quality poses some challenges with regard to the ruling process and the ion etching process. Our investigation and process results will be described here. Additionally, first results of the process on a grating substrate are demonstrated.